The Role of Family Support in Enhancing Illness Acceptance Among Heart Failure Patients - Prameswari, Shafa Textona; Kristinawati, Beti (Jurnal Kesehatan, 2025)
Heart failure is a chronic disease that has a significant impact on the physical and psychological condition of the patient. A critical aspect of disease management is illness acceptance, which is the patient's ability to accept their condition positively. Family support has a crucial role in helping patients undergo this acceptance process. This study aims to analyze the relationship between family support and acceptance of illness in heart failure patients. The method used in this study is correlative analysis with a quantitative approach, a sample of 149 respondents was collected using a purposive sampling technique. The research was conducted at the General Hospital of Surakarta. Research data were collected using demographic questionnaires, family support, and acceptance of illness (ais). The results showed a positive and significant relationship between family support and acceptance of illness in heart failure patients with a p-value of 0.007 (p <0.05). Patients receiving family support in the form of emotional, instrumental, appreciation, and informational have an acceptance level of illness compared to patients who lack support. Family support helps patients manage emotions, improve treatment adherence, and adjust to necessary lifestyle changes. The conclusion of this study confirms that family support plays an essential role in increasing acceptance of illness in heart failure patients. After obtaining a p-value of 0.007, which means (p < 0.05) the null hypothesis (ho) is rejected.